Contextualized cosmopolitanism: Human rights practice in South Korea - Yoon Jin Shin (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
There are three prominent criticisms directed against those engaging with human rights practice: First, the claim that human rights norms effectively erase the local in favor of an abstract universal; second, that human rights enterprises fail to appreciate its Western colonial continuities; and third, that the rights discourse functions predominantly in a top-down mode, drowning out the multitude of voices on the ground. Drawing on the dynamic aspects of human rights practices by and through the Constitutional Court of South Korea - which the paper understands as contextualized cosmopolitan human rights practices - this paper illustrates how such criticisms are too generalized. First, it illuminates the conflicts, struggles and innovations developed in the course of the court's engagement with international human rights norms: illuminating how the court incorporates the norm as a substantive standard for rights review, while defying a simple priority of international human rights law in a domestic legal order. Second, it examines the court's transforming self-identity reflected on and evolved through its engagement with foreign law and practice of human rights: observing the court's self-emancipation from a traditional focus on a few influential powers to a more inclusive comparative practice across wider jurisdictions of the world, and its effort to establish itself as a regional leader in human rights jurisprudence. Third, the practice of the court shows how rights discourse productively internalizes the tension between local traditions and universal standards. Finally, the paper underlines the role of individual rights-holders in the above contexts and argues that the empowerment and emancipation of the individual is a genuine effect of rights contestation and the rights review system. Through these contextualized and bottom-up cosmopolitan human rights practices, local rights actors concretize and advances the meaning and the operation of universal human rights norms in their specific contexts.
Keywords: 320; human rights; contextualized cosmopolitanism; international human rights law; foreign law; tradition; rights review; bottom-up rights practice; individual empowerment